Characterization of cyclic alternating pattern in infants with laryngomalacia - Cáceres, Laura Mendoza; Vargas, Ángel Daniel Santana; Rosas, Gabriela Millán; Pérez, Eduardo Barragán; Poblano, Adrián; Miranda, Rafael Santana (Sleep Science, 2022)
Objective Cyclic alternanting pattern (CAP) has been considered a marker of sleep instability in children. The aim of this study was to evaluate the CAP in infants with laryngomalacia.Material and Methods CAP were quantified in 15 infants with laryngomalacia (mean age 167.2±97.21 days) and 10 controls (mean age of 158.5±116.2 days) using polysomnography.Results The distribution of the A2 subtypes across NREM stages in infants with laryngomalacia showed a decrease, as well as in the mean duration of CAP sequences. The A3 CAP and arousals increased in infants with laryngomalacia. Our data showed a stronger correlation between the mean duration of A1 CAP and the age in healthy controls than in infants with laryngomalacia. In accordance to previous reports infants with laryngomalacia exhibited an increase in total awake time, apnea-hypopnea index, and a decrease in N3 stage compared to controls.Discussion Our findings add to a growing body of literature of CAP as an indicator of brain maturation
Keywords: Laryngomalacia; Sleep; Apnea; Infant; Newborn; Diseases